Causal relationship between domestic credit and international reserves: The experience of developing countries - Sanjeev Gupta (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1982)
Three causality tests, Haugh, Granger and Sims are used to determine the nature of causal relationship between the components of monetary base of India, Malaysia, Mexico and Taiwan. The conclusion derived is that bidirectional causality exists between the changes in domestic credit and changes in international reserves for all four countries.
Keywords: 330